Empirical predicted residual life of the base metal of MCP of WWER-1000 reactors in operation - Gozhenko, S.V. (Problems of Atomic Science and Technology, 2023)
The comprehensive analysis of the results of research by direct methods of BM of MCP of the South-Ukraine NPP after 100,000 and 200,000 h of operation was carried out. In BM with a fine-grained initial structure, the first stage of the aging process, accompanied by metal strengthening, is completed during the first 100,000 h of MCP operation; then the second stage begins, accompanied by decreasing of metal strength. In BM with a coarse-grained initial structure, the first stage of the aging process lasts more than 200,000 h of operation. The predicted residual resource of MCP is determined by the resource of BM with a fine-grained initial structure. The critical regulatory property at the first stage of the aging process of BM is relative elongation, at the second stage – the strength limit. Проведено комплексний аналіз результатів досліджень прямими методами основного металу (ОМ) ГЦТ Південно-української АЕС після 100 та 200 тис. год експлуатації. В ОМ з дрібнозернистою вихідною структурою перший етап процесу старіння, що супроводжується зміцненням металу, завершується впродовж перших 100 тис. год експлуатації ГЦТ, а потім починається другий, що супроводжується зниженням міцності металу. В ОМ з крупнозернистою вихідною структурою перший етап процесу старіння триває 200 тис. год експлуатації. Розрахунки прогнозованого залишкового ресурсу показали, що ресурс ГЦТ визначається ресурсом ОМ з дрібнозернистою вихідною структурою. Впродовж перших 100 тис. год експлуатації ГЦТ критичною нормованою властивістю є відносне подовження, впродовж других – межа міцності.